Evaluation of testis sparing surgery in paediatric testicular tumor (Journal of Paediatric Surgeons of Bangladesh, 2023)
Aim: To evaluate the outcome of testis sparing surgery (TSS) and to investigate under which circumstances TSS can be considered a safe treatment option in paediatric patient with testicular tumor.Methods & Materials: This prospective interventional study was conducted in Dhaka Medical College Hospital (DMCH) during January 2019 to June 2021 (total 30 months) and 0-14 years child with testicular tumor was included & child with advanced disease was excluded. Total 30 patients were selected with consecutive sampling. Postoperatively patients were followed up for 6 months. Results: Germ cell tumor (GCT) was the most common (93.3%) paediatric testicular tumor and teratoma was the commonest among the GCT (76.7%). Benign tumor was predominant (83.3%) in paediatric testicular tumor and TSS was done in this group. No tumor recurrence or testicular atrophy occurred in 6 months follow-up.Conclusion: TSS to preserve testis is preferable for paediatric testicular tumor.Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1 & 2): 8-12